Title page from Le diverse et artificiose machine del capitano Agostino Ramelli [The Various and Ingenious Machines of Captain Agostino Ramelli] - Ramelli, Agostino (Le diverse et artificiose machine del capitano Agostino Ramelli, 1588)
The book's title is set within an architectural frame embellished with antique ornamental motifs, weapons, armor, and symbols of warfare and siege. This title page is a facsimile reproduction, hence the lower quality of the image.
Keywords: Title pages; Machinery